Shell Measurements and Mold Thermal Mapping Approach to Characterize Steel Shell Formation in Peritectic Grade Steels. Issue 1 (17th September 2021) - Balogun, Damilola; Roman, Muhammad; Gerald, Rex E.; Huang, Jie; Bartlett, Laura; O'Malley, Ronald
Abstract : Herein, the prospects of detecting peritectic behavior in carbon steels (Fe–C) using solidified shell thickness measurements and real‐time mold thermal maps are investigated. Irregular steel shell thickness and localized shell thinning are negative conditions associated with the peritectic transformation in many steel grades. Detailed three dimensional (3D) thickness maps are generated to directly contrast peritectic from nonperitectic solidification features using a laboratory dip test. Characterization of the steel shell also includes measurement of 3D shell surface deviations from a nominally flat surface. The unevenness parameter, which is calculated using the coefficient of variation in shell thickness as a function of the carbon content in the steel, clearly peaks around 0.14%C. A distributed fiber‐optic sensor, embedded 1 mm from the working face of a 100 × 55 × 12 mm 3 thick copper chill block, has been used to obtain real‐time mold thermal maps of the solidification event during immersion of the block into molten steel. A programmable drive is used to control the motion of the chill block during immersion into a steel bath to minimize variability in immersion speed, position, and time. The thermal mapping measurements are well correlated with the shell profile measurements. Abstract : Based on thickness measurments of steel shell and real‐time mold thermal maps with fiber‐optic sensors, peritectic behavior is identified in Fe–C steels. The measurement of shell thickness uses high‐resolution metrology grade optical scanner to reproduce accurate 3D model of the steel shell from which thickness measurements and shell surface deviation are evaluated.